Age-related histomorphometric and ultrastructural changes in the Sertoli cells of Japanese quail (Coturnix Coturnix japonica). (December 2021) - Molele, Reneilwe A.; Mahdy, Mohamed A.A.; Zakariah, Musa; Ibrahim, Mohammed I.A.; Fosgate, Geoffrey T.; Brown, Geoffrey
Highlights: Age-related ultrastructural and morphometric changes in Japanese quail testes. Apoptotic Sertoli cells observed in pre-pubertal and aged quail. The Sertoli cell number (SCN) in the Japanese quail decreases post adulthood. Decline in the SCN in the aged group suggest a decline in spermatogenesis. SCN in Japanese quail strongly correlated with seminiferous epithelial height (SEH). Abstract: Prepared sections from pre-pubertal, pubertal, adult, and aged Japanese quail testes were examined by light microscopy and transmission electron microscopy (TEM) and measurements of seminiferous tubular diameter (STD), luminal diameter (SLD), epithelial height (SEH) and cross-sectional area of the seminiferous tubules (AST) were taken using an image analyzer. Apoptotic Sertoli cells with features such as cell shrinkage and chromatin condensation were observed in pre-pubertal and aged quail. There was a significant difference between the mean Sertoli cell number (SCN), SLD, SEH, STD and AST among the four age groups ( P < 0.001). The highest SCN (mean ± standard error) was recorded in the adult (30.53 ± 0.42), with the aged group displaying the lowest mean (11.80 ± 0.27) SCN. Spearman's rho correlation coefficients demonstrated a strong relationship between the SCN and SEH in the pubertal (ρ=0.915; P < 0.001), adult (ρ=0.878; P < 0.001), and aged (ρ=0.858; P < 0.001) groups, while a significant moderate correlation was observed in the pre-pubertal (ρ=0.606; P < 0.001) group. There were significant moderate correlations between the SCN and STD in the pre-pubertal (ρ=0.445; P < 0.001), pubertal (ρ=0.653; P < 0.001), adult (ρ=0.440; P < 0.001), and aged (ρ=0.514; P < 0.001) groups. Furthermore, significant moderate correlations were estimated between the SCN and AST in the pre-pubertal (ρ=0.453; P < 0.001), pubertal (ρ=0.661; P < 0.001), adult (ρ=0.393; P = 0.001), and aged (ρ=0.498; P < 0.001) groups. This study provides baseline data on the morphology and development of the Sertoli cell, as well as testicular morphometry in avian species during the pre-pubertal, pubertal, adult, and aged stages using the Japanese quail as a model.